2014
DOI: 10.1111/jgh.12708
|View full text |Cite
|
Sign up to set email alerts
|

Potential synergistic anti‐tumor activity between lenalidomide and sorafenib in hepatocellular carcinoma

Abstract: Lenalidomide can enhance the anti-tumor effects of sorafenib in HCC through its immune modulatory effects, and CD8(+) TILs play an important role in the anti-tumor synergism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…This leads to T cell activation, promotion of Th1 T cell differentiation, and repair of defects in immune synapse formation . We have also found that lenalidomide can enhance cytotoxic T cell activity in the tumour micro‐environment using an orthotopic liver cancer mouse model . The potential effects of lenalidomide on other immune cells remain undetermined, and many analogs of lenalidomide have been developed to pursue better immune‐modulatory efficacy …”
Section: Discussionmentioning
confidence: 89%
“…This leads to T cell activation, promotion of Th1 T cell differentiation, and repair of defects in immune synapse formation . We have also found that lenalidomide can enhance cytotoxic T cell activity in the tumour micro‐environment using an orthotopic liver cancer mouse model . The potential effects of lenalidomide on other immune cells remain undetermined, and many analogs of lenalidomide have been developed to pursue better immune‐modulatory efficacy …”
Section: Discussionmentioning
confidence: 89%
“…VEGF blockade can improve dendritic cell differentiation [11] and synergize with immunotherapy [12]. In preclinical models, lenalidomide enhanced the antitumor activity of sorafenib, presumably through immune modulation and increased CD8 + of tumor infiltrating lymphocytes (TILs) and decreased T regs among TILs [13]. …”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%
“…Spheroids were harvested into the standard 96-well plates, and measured by MTT assay. The cell cycle distribution and extent of apoptosis were evaluated by staining the cells with propidium iodide (50 μg/mL) in the presence of RNase A (100 units/mL) and measured by flow cytometry [24]. For the colony formation assay, the cells were seeded into 6-well plates (6 × 10 3 cells/well) and maintained in medium for 14 days, with medium changes every 4 days.…”
Section: Establishment Of Pd-l1-expressing Mouse Liver Cancer Cellsmentioning
confidence: 99%
“…Tumor weights were measured after 21 days of treatment. At the end of treatment, blood samples were collected to measure hemogram and biochemistry, and formalin-fixed, paraffin-embedded tumor samples were collected for analysis of tumor apoptosis (transferase deoxytidyl uridine end labeling [TUNEL] assay), microvessel density, and tumor proliferation (immunohistochemical staining) [24]. To evaluate the roles of CD8+ T cells in the antitumor efficacy of anti-PD1 antibodies and sorafenib, CD8+ T cells were depleted by intraperitoneal injection of anti-CD8 antibody (clone 53-6.72) or isotype control antibody (clone 2A3 or HRPN) (Bio X Cell), respectively.…”
Section: Drug Treatment and Efficacy/safety Evaluationmentioning
confidence: 99%